A data‐driven approach to complement the A/T/(N) classification system using CSF biomarkers - Hernández‐Lorenzo, Laura; Gil‐Moreno, Maria José; Ortega‐Madueño, Isabel; Cárdenas, Maria Cruz; Diez‐Cirarda, Maria; Delgado‐Álvarez, Alfonso; Palacios‐Sarmiento, Marta; Matias‐Guiu, Jorge; Corrochano, Silvia; Ayala, José L.; Matias‐Guiu, Jordi A. (CNS neuroscience & therapeutics, 2024)
Aims The AT(N) classification system not only improved the biological characterization of Alzheimer's disease (AD) but also raised challenges for its clinical application. Unbiased, data‐driven techniques such as clustering may help optimize it, rendering informative categories on biomarkers' values. Methods We compared the diagnostic and prognostic abilities of CSF biomarkers clustering results against their AT(N) classification. We studied clinical (patients from our center) and research (Alzheimer's Disease Neuroimaging Initiative) cohorts. The studied CSF biomarkers included Aβ(1–42), Aβ(1–42)/Aβ(1–40) ratio, tTau, and pTau. Results The optimal solution yielded three clusters in both cohorts, significantly different in diagnosis, AT(N) classification, values distribution, and survival. We defined these three CSF groups as (i) non‐defined or unrelated to AD, (ii) early stages and/or more delayed risk of conversion to dementia, and (iii) more severe cognitive impairment subjects with faster progression to dementia. Conclusion We propose this data‐driven three‐group classification as a meaningful and straightforward approach to evaluating the risk of conversion to dementia, complementary to the AT(N) system classification. We compared CSF biomarkers clustering results against their AT(N) classification in two cohorts. Clustering yielded three groups: non‐defined AD, early stages with delayed risk of dementia, and severe cognitive impairment subjects with faster progression to dementia. We propose this data‐driven categorization as a meaningful and straightforward approach to evaluating dementia risk, complementary to the AT(N) system classification.